Ismail Kadare's views on Albanian epic culture and folklore in the literary work "Autobiography of the people in verse" - Kastrati, Nexhmije (Technium Social Sciences Journal, 2022)
It is about one of the literary works discussed numerous times and in many literary dimensions, both national and international, that looks into the efforts, phenomena, history, and naturalness of the Albanian popular culture in front of the great European cultures, particularly those of Balkan countries. The great writer Kadare, who had entered through the great gates in the most important national and historical events and had penetrated very deeply into the social life and the psychology of his people, indeed, would not happen to be by chance and unexpectedly in the rich field of Albanian folk creativity. In the process of research, popular creativity remains a life-force and inspiration passed down from one generation to another. As he puts it "When you browse folk poetry, you experience a sense of eternity, reality, space. You want to live, to love, to have children, to be a mother, to be a father, to be a son-in-law, to go to war, to return from her, even to die as in a song”. Culture, poetry and popular prose in Albanian literature are emphasized in these writings, in particular, in those that have a national character, and thereby even communicate freely and strongly with artistic literature like nowhere else.